The Effect of Hole Width on Full Height Rectangular Opening Castellated Steel Beam with Diagonal Stiffener Concerning Its Flexural Capacity - Muhamad Rusli A.; Prabowo Setiyawan; Dessy Maimunah; Destia Wulandari (JACEE (Journal of Advanced Civil and Environmental Engineering), 2019)
The use of a diagonal stiffener in a full height rectangular opening castellated steel beam can prevent the failure mechanism of vierendeel. This results in the flexural capacity of the castellated beam higher than the original IWF profile. The flexural capacity of a castellated steel beam can be optimized by designing the hole width on the web section. This research aims to find out the effect of several values of castellated steel beam hole width on the flexural capacity. In this research, there are 4 castellated steel beam models whose flexural capacity values are calculated using the truss analysis and pushover analysis methods. Based on the calculation results, it can be concluded that the smaller the value of the hole width, the greater the flexural capacity of the castellated steel beam will be. The largest increase in flexural capacity from the original IWF to the castellated beam is 140.93%.